Measurement of the tensor analyzing power T20 for incoherent π− photoproduction on a deuteron above the first resonance region; Physics Letters B; Vol. 860 - Gauzshtein V. V. Vyacheslav Valerjevich; Darwish E. M. Eed; Fiks (Fix) A. I. Alexander Ivanovich; Kuzin M. Ya. Matvey Yaroslavovich; Levchuk M. I. Mikhail Ivanovich; Loginov A. Yu. Aleksey Yurjevich; Nikolenko D. M. Dmitry Mitrofanovich; Rachek I. A. Igor Anatoljevich; Shestakov Yu. V. Yury Vladimirovich; Toporkov D. K. Dmitry Konstantinovich; Yurchenko A. V.; Vasilishin B. I. Bogdan Ivanovich; et al. (2025, 2025)
Title screen